Transformasi Bisnis di Era Digital: Peran Vital Digital Marketing dalam Kesuksesan Bisnis pada Bonassa Collection - Pratama, Krisna Rahmadani; Ikaningtyas, Maharani (Jurnal Bisnis Indonesia, 2024)
The fashion industry stands out as one of the most dynamic and competitive sectors in the currentdigital era. In this context, the significance of digital marketing in establishing and sustaining afashion business has grown significantly. This journal article delves into the vital role of digitalmarketing in fashion business growth, with a particular focus on the Bonassa Collection as asuccessful case study. This research explores various digital marketing strategies employed byBonassa Collection to attain success in this challenging market. We delve into various aspects ofdigital marketing, including social media, online advertising campaigns, and online brand building.Keywords: Digital Marketing; Fashion Business; Marketing Strategies; Online Brand Building